[Sigma]: the long and short of it - Robert S. Chirinko (Center for Economic Studies and ifo Institute (CESifo), 2008)
Research on the elasticity of substitution between capital and labor - ó - has been proceeding for 75 years. While there is clearly a strong case for the importance of ó in the analysis of growth and other economic issues, much less agreement exists on the value of ó. This paper offers some perspectives on prior estimates of ó, emphasizing the fundamental tension between the short-run data that are available and the long-run parameter that is required. Estimates of ó based on various short-run and long-run models are discussed and, while the estimates range widely, the weight of the evidence suggests a value of ó in the range of 0.40 to 0.60. There is little evidence to sustain the assumption of a Cobb-Douglas production function.
Keywords: E22; C20; 330; production; function; capital formation; economic growth; estimating long-run relations; Wirtschaftswachstum; Prognoseverfahren; Investition; Cobb-Douglas-Produktionsfunktion; Schätztheorie